Garap Sanggit Pakeliran Padat Lakon Bima Bungkus Sajian Ki Bambang Suwarno - Catur Nugroho; Yudha Ibnu Mutaqin (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2023)
This research departs from the assumption that “sanggit lakon” is one of the main elements of work in Pakeliran Padat. The forms of Pakeliran Padat have room for creativity and expression that is broad, complicated, and/or even limitless. The puppeteer as the main creator has the freedom to work on the sanggit lakon based on his sensitivity and accuracy in observing the phenomena that occur. This research aims to find out what is related to Sanggit Lakon Bima Bungkus in Pakeliran Padat. This is important as a stimulant for artistic research studies, especially discussions regarding concepts and work in Pakeliran Padat. Ki Bambang Suwarno’s lakon Bima Bungkus was chosen as a case study research object which was deemed representative of the analysis needs. The approach used is the basic concept of Pakeliran Padat, the concept of sanggit garap lakon, the basic aesthetic concept of puppetry nuksma and mungguh, as well as the application of hermeneutics analysis. The qualitative descriptive data analysis method is carried out by observing the validity of the data through data triangulation and method triangulation. It is hoped that the collection of appropriate data through literature study, interviews and observations will be able to explain the work of the lakon Bima Bungkus in Pakeliran Padat presented by Ki Bambang Suwarno. Based on the discussion that has been carried out, it shows that the pakeliran padat of Ki Bambang Suwarno’s lakon Bima Bungkus is produced using the concept of pakeliran padat. The garap lakon is presented in a complex manner with a focus on Bima’s characterization as the main character. Garap catur includes janturan, pocapan, and ginem and also implements the concept of garap padat, namely conveying it effectively, efficiently, and focusing on the main problem of the scene. Garap sabet presents thematic puppet movements which represent garap padat. Through thematic sabet, events of lakon can be visualized through a series of unique, distinctive and meaningful wayang movements. Meanwhile, garap karawitan pakeliran presents musical compositions that are packaged for the needs of the events of lakon, although the vocabulary for the musical compositions still comes from traditional musical compositions.